Identification of the economic security technological component of Ukraine in the field of railway transport - Shevchenko, A. (Економічний вісник Донбасу, 2016)
There was conducted an integral evaluation of the technological component of economic security of Ukraine in the field of railway transport using modern methodology. There were estimated normalizing, threshold, optimum values, weighting factors and expectation indicators.